PENGARUH INTELLECTUAL INTELLIGENCE, EMOTIONAL INTELLIGENCE DAN SIKAP KERJA TERHADAP KINERJA GURU MAN 16 JAKARTA - Andriani Suryanata (2022)
This research is a quantitatived researchs which aims to determine whether there is an influence between Intellectual Intelligence, Emotional Intelligence and Work Attitudes towards Teachers at MAN 16 Jakarta. This study used 43 teachers as respondents using a sampling technique with saturated sampling. The analysis technique used is path analysis method and data processing is done through SmartPLS 3.0. From the test, it was found that (1) Intellectual Intelligence had a significant effect on the performance of MAN 16 Jakarta Teachers. (2) Emotional Intelligence had no significant effect on the performance of MAN 16 Jakarta Teachers. (3) Work Attitudes had no significant effect on the performance of MAN 16 Jakarta Teachers.